2021
DOI: 10.1186/s12885-021-08186-9
|View full text |Cite
|
Sign up to set email alerts
|

Dichloroacetate and PX-478 exhibit strong synergistic effects in a various number of cancer cell lines

Abstract: Background One key approach for anticancer therapy is drug combination. Drug combinations can help reduce doses and thereby decrease side effects. Furthermore, the likelihood of drug resistance is reduced. Distinct alterations in tumor metabolism have been described in past decades, but metabolism has yet to be targeted in clinical cancer therapy. Recently, we found evidence for synergism between dichloroacetate (DCA), a pyruvate dehydrogenase kinase inhibitor, and the HIF-1α inhibitor PX-478. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…Previous studies have shown that DCA is a pharmacological agent that activates PDH by inhibiting PDK and also shows significant neuroprotective potential. The administration of DCA has been suggested to facilitate local lactic acid removal [ 32 ], tumor therapy [ 33 ], and pulmonary hypertension [ 34 ]. However, the protective effect, molecular mechanism, and blood-brain barrier permeability of DCA in cerebral IS and I/R injury have been rarely investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that DCA is a pharmacological agent that activates PDH by inhibiting PDK and also shows significant neuroprotective potential. The administration of DCA has been suggested to facilitate local lactic acid removal [ 32 ], tumor therapy [ 33 ], and pulmonary hypertension [ 34 ]. However, the protective effect, molecular mechanism, and blood-brain barrier permeability of DCA in cerebral IS and I/R injury have been rarely investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Synergism has been reported when DCA is combined with different drugs for anti-cancer research: DCA/cisplatin or gefitnib or elotinib ( Al-Azawi et al, 2021 ), DCA/metformin ( Kim et al, 2021 ; Klose et al, 2021 ; Korsakova et al, 2021 ), DCA/3-bromopyruvate ( Nikravesh et al, 2021 ), DCA/sorafenib ( Sun et al, 2021 ), DCA/PX-478 ( Parczyk et al, 2021 ) and DCA/erlotinib ( Dyrstad et al, 2021 ). Said synergistic effect has also been observed when Nic is combined with other agents: Nic/gemcitabine ( Guo et al, 2022b ), Nic/metformin ( Kang et al, 2021 ) and Nic/doxorubicin ( Lohiya and Katti, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…DCA has been shown to elevate hydrogen peroxide ( Xie et al, 2011 ) and ROS ( Kumar et al, 2012 ; Duan et al, 2013 ; Kim et al, 2021 ; Klose et al, 2021 ; Nikravesh et al, 2021 ). In addition, ROS is increased when DCA is combined with sorafenib ( Sun et al, 2021 ) or PX-478 ( Parczyk et al, 2021 ). Nic also increases ROS ( Zhou et al, 2017 ; Shangguan et al, 2020 ; Kaushal et al, 2021 ; Lohiya and Katti, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, in recent years, no additional clinical studies on PX-478 have been reported, and more studies on PX-478 in combination with other drugs are needed to reduce the side effects of the drug itself and improve efficacy. The combination of DCA and PX-478 demonstrated synergistic effects in a variety of cancers, inhibiting cancer proliferation through the production of ROS and apoptosis ( 110 ). Currently, phase I clinical trials are ongoing in patients with advanced solid tumors.…”
Section: Control Of Cellular Metabolism As a Target For Cancer Therapymentioning
confidence: 99%